Catalytic Dehydrogenative Coupling of Hydrosilanes with Alcohols for the Production of Hydrogen On‐demand: Application of a Silane/Alcohol Pair as a Liquid Organic Hydrogen Carrier. Issue 45 (26th July 2017) - Ventura‐Espinosa, David; Carretero‐Cerdán, Alba; Baya, Miguel; García, Hermenegildo; Mata, Jose A.
Abstract: The compound [Ru( p ‐cym)(Cl)2 (NHC)] is an effective catalyst for the room‐temperature coupling of silanes and alcohols with the concomitant formation of molecular hydrogen. High catalyst activity is observed for a variety of substrates affording quantitative yields in minutes at room temperature and with a catalyst loading as low as 0.1 mol %. The coupling reaction is thermodynamically and, in the presence of a Ru complex, kinetically favourable and allows rapid molecular hydrogen generation on‐demand at room temperature, under air, and without any additive. The pair silane/alcohol is a potential liquid organic hydrogen carrier (LOHC) for energy storage over long periods in a safe and secure way. Silanes and alcohols are non‐toxic compounds and do not require special handling precautions such as high pressure or an inert atmosphere. These properties enhance the practical applications of the pair silane/alcohol as a good LOHC in the automotive industry. The variety and availability of silanes and alcohols permits a pair combination that fulfils the requirements for developing an efficient LOHC. Abstract : On demand ! An effective supported ruthenium catalyst on the surface of rGO controls the hydrogen production from hydrosilanes. The hydrogen storage properties show the potential application of the silane/alcohol pair as an efficient liquid organic hydrogen carrier.